The interrelationship between periodontal disease and patients with Down Syndrome - an integrative literature review (Research, Society and Development, 2021)
The present work is an integrative literature review with the aim of evaluating the relationship between periodontal disease and patients with Down Syndrome (DS). Data were collected through a complete search carried out in the Pubmed and Science Direct databases, using the descriptors Down Syndrome, Periodontitis and Oral Health, which were inserted in the platform in a crossed manner with the Boolean expression “and”. The combination of descriptors in the databases resulted in 77 studies. Of these, 73 did not meet the inclusion criteria previously established, leaving four articles for review and complete reading. The results of the studies show that the severity of periodontal disease increases over the years in patients with DS. Of the analyzed studies, 100% agree that there is a predisposition to develop periodontal disease and other oral problems in patients with Down Syndrome, regardless of the level of hygiene, thus reinforcing the need for frequent visits to the dentist, to assist in prevention and ensure a better quality of life for these individuals.